Raven's gate - Horowitz, Anthony (London : Walker Books, 2005)
Sent to live in a foster home in a remote Yorkshire village, Matt, a troubled fourteen-year-old English boy, uncovers an evil plot involving witchcraft and the site of an ancient stone circle.
Keywords: Foster home care -- Fiction; Identity -- Fiction; Stone circles -- Fiction; Supernaturel -- Fiction; Witches -- Fiction